2017
DOI: 10.1113/ep086076
|View full text |Cite
|
Sign up to set email alerts
|

Functional capacity in a rat model of heart failure: impact of myocardial infarct size

Abstract: What is the central question of this study? To the best of our knowledge, no studies have evaluated oxygen uptake, carbon dioxide production and exercise tolerance in rats that have undergone myocardial infarction classified by myocardial infarct (MI) size. What is the main finding and its importance? Oxygen uptake and exercise intolerance are MI size dependent, and classification based on MI size can distinguish rats with functional capacity impairment. Rats with a large MI (>40% of the left ventricle) might … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 49 publications
(104 reference statements)
0
4
0
Order By: Relevance
“…Reduction of fractional shortening by greater than 50% has been shown to exhibit a heart failure phenotype in preclinical models and was used to define an excessive reduction in cardiac function. 24 The IC 10 value determined in the echo study represented our estimation of a beneficial in vivo effect that was later confirmed in human testing. 10 Aficamten had a shallow concentration−response profile with an IC 50 /IC 10 ratio of 9.9×, whereas mavacamten had a steeper concentration−response profile with an IC 50 /IC 10 ratio of 2.8×.…”
Section: ■ Results and Discussionmentioning
confidence: 83%
See 1 more Smart Citation
“…Reduction of fractional shortening by greater than 50% has been shown to exhibit a heart failure phenotype in preclinical models and was used to define an excessive reduction in cardiac function. 24 The IC 10 value determined in the echo study represented our estimation of a beneficial in vivo effect that was later confirmed in human testing. 10 Aficamten had a shallow concentration−response profile with an IC 50 /IC 10 ratio of 9.9×, whereas mavacamten had a steeper concentration−response profile with an IC 50 /IC 10 ratio of 2.8×.…”
Section: ■ Results and Discussionmentioning
confidence: 83%
“…The therapeutic window was defined by the IC 50 /IC 10 ratio in the echocardiography experiment and corresponded to compound concentrations that reduced FS by 50% (IC 50 ) and 10% (IC 10 ), with a higher IC 50 /IC 10 ratio predictive of a greater therapeutic window. Reduction of fractional shortening by greater than 50% has been shown to exhibit a heart failure phenotype in preclinical models and was used to define an excessive reduction in cardiac function . The IC 10 value determined in the echo study represented our estimation of a beneficial in vivo effect that was later confirmed in human testing .…”
Section: Results and Discussionmentioning
confidence: 99%
“…[9][10][11] In brief, rats were anesthetized by intraperitoneal injection of 2% pentobarbital sodium (2 mL/kg) for left thoracotomy and pericardiotomy. [9][10][11] In brief, rats were anesthetized by intraperitoneal injection of 2% pentobarbital sodium (2 mL/kg) for left thoracotomy and pericardiotomy.…”
Section: Modelmentioning
confidence: 99%
“…Establishment of MI model was carried out as described. [9][10][11] In brief, rats were anesthetized by intraperitoneal injection of 2% pentobarbital sodium (2 mL/kg) for left thoracotomy and pericardiotomy. Under aseptic conditions, skin preparation was carried out first.…”
Section: Modelmentioning
confidence: 99%